Campus Selection Procedure Android App Project - V.Indhumathi Durairaj,Dr. P. Malathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This project is intended to create a web application for university training majors. A system is a web application that, if properly launched, can be accessed throughout the organization and beyond. This system can be used as a university degree application (implementation supervisor) to handle student training information Participants must be able to submit their CV. Visitors/company representatives and students can find/search all information submitted.